Three decades of innovation in employment policies for people with mental health problems (1991-2021): occupational rehabilitation, supported employment and recovery of citizenship - Valmorisco Pizarro, Segundo; de Fuentes García-Romero de Tejada, Carlos (Cuadernos de Relaciones Laborales, 2024)
This article analyzes the degree of compliance with the principles of the IPS (Individual Placement and Support) model of supported employment established by Bond, Drake and Becker (IPS Employment Center, USA) in the Labor Rehabilitation Centers (CRL) of the Community of Madrid. For these authors, success in hiring people with serious mental health problems involves identifying which factors create vocational facilitators for achieving and maintaining employment. The analysis based on the exploitation of data from activity reports and in-depth interviews and focus groups, carried out with patients, family members and staff of said centers, indicates that five of these principles are met in the work rehabilitation model and that there should be a readjustment of this model towards the recovery of the person (comprehensive approach beyond employment), improving compliance with some of the principles of the IPS model.